FORMATION OF SPEECH COMPETENCE IN PRESCHOOLERS BASED ON GAME ACTIVITIES - Adkhamjonova Mohlarbonu (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract. In this article, the author emphasizes the role and importance of play activities of preschoolers in the formation of speech competence. Pedagogy considers various possibilities of using play activities to form various knowledge, skills and abilities in a child, forms of organizing a game in a kindergarten group in order to develop practical recommendations for educators and parents taking into account age characteristics.